Removal of the endoplasma membrane upon sperm cell activation after pollen tube discharge - Sugi, Naoya; Izumi, Rie; Tomomi, Shun; Susaki, Daichi; Kinoshita, Tetsu; Maruyama, Daisuke (Frontiers in Plant Science, 2023)
In pollen and pollen tubes, immotile sperm cells are enclosed by an inner vegetative plasma membrane (IVPM), a single endomembrane originating from the vegetative-cell plasma membrane. It is widely believed that sperm cells must be removed from the IVPM prior to gamete associations and fusions; however, details of the timing and morphological changes upon IVPM dissociation remain elusive. Here, we report a rapid IVPM breakdown immediately before double fertilization in Arabidopsis thaliana. The IVPM was stably observed in coiling pollen tubes when pollen tube discharge was prevented using lorelei mutant ovules. In contrast, a semi-in vivo fertilization assay in wild-type ovules demonstrated fragmented IVPM around sperm nuclei 1 min after pollen tube discharge. These observations revealed the dynamic alteration of released sperm cells and provided new insights into double fertilization in flowering plants. With a summary of recent findings on IVPM lipid composition, we discussed the possible physiological signals controlling IVPM breakdown.